VD_FINDINFO HC / 2013 / 246 vom 26. März 2013 - VD Tribunal cantonal (2013)
OBLIGATION D'ENTRETIEN, CONJOINT, ENFANT, PROTECTION DE L'UNION CONJUGALE | 163 CC, 176 al. 1 ch. 1 CC, 308 al. 1 let. b CPC (CH)